SISTEM PENDUKUNG KEPUTUSAN UNTUK MENGEVALUASI KINERJA DOSEN PRODI DI STIKOM UYELINDO KUPANG MENGGUNAKAN METODE TOPSIS - Bisilisin, Franki Yusuf; Naatonis, Remerta R. (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2019)
STIKOM Uyelindo Kupang was established in the year 2000 as an information technology-based tertiary institution which has three study programs, namely under graduate of informatics engineering, diploma three informatics engineering and under graduate of information systems. The three study programs always strive to improve the status of accreditation by continuously improving internal quality and making accreditation a strategy to compete with other universities. To maintain quality, STIKOM Uyelindo Kupang, especially the undergraduate informatics engineering study program routinely monitors and evaluates the performance of lecturers. The problem that is often faced in routine monitoring and evaluation of lecturer performance is the performance evaluation process that is still objective so that to overcome these problems, a decision support system is needed that can assist in evaluating the performance of lecturers at STIKOM Uyelindo Kupang. The purpose of this study is to make a decision support system for the assessment of performance of lecturers of the first-degree informatics engineering study program at STIKOM Uyelindo Kupang using TOPSIS method. The results of this study are in the form of a desktop-based application that can facilitate the monitoring and performance evaluation teams of lecturers in evaluating the performance of lecturers of study programs